Fizicheskaya i sportivnaya kultura: soderzhanie, vzyaimosvyazii i dissotsiatsii - Lubysheva, L. I. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The important fact in the modern world is the increasing comprehension of physical culture as part of the general culture of the personality and the society. However alongside with the standard and clear for the majority of people the phenomenon of physical culture arises and develops, getting the independent status the phenomenon of sport. It is multifased and the multifunctional phenomenon which hardly entering in the uniform concept. It is enough to tell, that people categorize as sports yachting, chess, airmodelling sports, and many other things where the nucleus of the activity becomes competition and the achievement of the victory. The intensity of these connections will accrue in the near future. New champions who grow from system of physical culture are necessary for sports; new technologies of the development of the physical potential of the personality are necessary for the physical culture. All of this is in social institute of physical culture and sports. It is required only that the new generation of experts understood methodological differences of phenomena of physical culture and sports and could realize in practice so necessary integration of sports culture and physical culture.